Risk Limiting Based Resilient Operation Method for Power Grid - Xiyue WANG; Hao ZHANG; Chaoyi PENG (Zhongguo dianli)
Under the background of construction of the new power system, the integration of a large amount of renewable energy into the existing grid poses significant challenges to the dispatch and operation mode of power grid. In order to address the risk of load shedding caused by the power fluctuation and uncertainty of renewable energy on real-time power balance in the grid, we propose a resilient operation model for the grid based on risk limiting theory (RLB). To solve the problem of solving probabilistic constraints, a solution is provided to enhance the operational resilience of the grid. By deriving three intermediate state models of RLB and their analytical solutions, we present an iterative RLB solution algorithm based on intermediate state models and provide a rigorous proof of its global optimality. Finally, based on the IEEE 6-node system and an actual 25981-node regional grid examples, we analyze the relationship between system flexibility, prediction accuracy, and system resilience, and it is concluded that improving the operational resilience of the new power system is premised on sufficient system flexibility and prediction accuracy.